2019
DOI: 10.24018/ejbmr.2019.4.5.115
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality Towards Bank Customer Loyalty (Empirical Study at BNI USU Medan)

Abstract: This study aims to analyze the influence of service quality on customer loyalty at PT. BNI (Persero), Tbk USU Medan. This study used a quantitative approach with an explanatory type of research. The sample were 120 respondents and processed statistically using simple linear regression method. The results show that service quality positively has a significant effect on customer loyalty. These findings indicate that good service quality will encourage the interest of customers to conduct transactions continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Previous researchers have found that service quality has a positive and significant effect on customer loyalty and it has been identified as a determinant construct of customer loyalty [5], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have found that service quality has a positive and significant effect on customer loyalty and it has been identified as a determinant construct of customer loyalty [5], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Parasuraman et al (1988) mengatakan bahwa service quality adalah seberapa jauh perbedaan antara kenyataan dan harapan pelanggan atas pelayanan yang mereka terima. Kualitas pelayanan yang baik dan efektif akan meningkatkan berdampak pada kepuasan dan loyalitas konsumen (Harahap et al, 2019).…”
Section: Aunclassified